2011
DOI: 10.1590/s0100-67622011000500014
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica de uma comunidade arbórea após enchente em fragmentos florestais no sul de Minas Gerais

Abstract: RESUMO -Com o objetivo de avaliar o impacto de uma enchente de grandes proporções sobre os indivíduos arbóreos, foi realizada, no ano de 2007, a avaliação de uma área aluvial localizada em São Sebastião da Bela Vista, MG, onde foram amostrados cinco fragmentos aluviais e uma floresta ciliar, inventariados inicialmente em 2005. Os resultados indicaram que, após a enchente, a dinâmica no curto-prazo foi caracterizada por taxa de mortalidade superior à de recrutamento e taxa de perda maior do que a de ganho em ár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(32 reference statements)
1
2
0
10
Order By: Relevance
“…The fact that there was no structural degradation process, which is characterized by a reduction in the number of trees and basal area, as once observed in other areas with chronic disturbances similar to those occurring in the forest under study (Machado and Oliveira Filho, 2010;Silva et al, 2011), suggests that disturbances intensity may be a determining factor and/or that forest formations may have different levels of resilience and resistance to disturbances. Considering the studies published by Orihuela et al (2015) and Reis et al (2014), one can indeed inferred that MOF is mainly formed by a group of stresstolerant species with Araucaria angustifolia as one of its representatives.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The fact that there was no structural degradation process, which is characterized by a reduction in the number of trees and basal area, as once observed in other areas with chronic disturbances similar to those occurring in the forest under study (Machado and Oliveira Filho, 2010;Silva et al, 2011), suggests that disturbances intensity may be a determining factor and/or that forest formations may have different levels of resilience and resistance to disturbances. Considering the studies published by Orihuela et al (2015) and Reis et al (2014), one can indeed inferred that MOF is mainly formed by a group of stresstolerant species with Araucaria angustifolia as one of its representatives.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, it is possible to observe a degradation process, synthesized by the reduction of individuals and basal area, in forests subject to intense or chronic disturbances. Some authors have observed these patterns in forest remnants subject to cattle presence and selective logging in Minas Gerais, Brazil (Machado and Oliveira Filho, 2010); in a transition forest between the Brazilian Cerrado and the Amazon, suggesting the influence of a strong drought as a determining factor (Mews et al, 2011); and in alluvial forest remnants subject to anthropic disturbances, after a heavy flood in the south of Minas Gerais, Brazil (Silva et al, 2011). Moreover, studies carried out in transformed landscapes have shown that disturbances caused by selective logging without planning and/or cattle grazing have negatively influenced richness by favoring pioneer species rather than late ones and therefore either slowing the process of succession down or limiting it (Clark and Covey, 2012;Zamorano-Elgueta et al, 2014;Arroyo Rodríguez et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…De acordo com Chagas et al (2001), o aumento líquido da área basal dos indivíduos, apesar da redução da densidade, é compatível com o processo de autodesbaste, no qual a dimensão média e a biomassa total dos indivíduos aumentam à medida que a densidade decresce. O autodesbate está frequentemente associado às fases avançadas de regeneração pós-distúrbios (Oliveira Filho et al 2007;Werneck & Franceschinelli 2004) Silva et al (2011) estudando fragmentos florestais no Sul de Minas Gerais, constataram que a dinâmica após a enchente foi caracterizada por taxa de mortalidade superior à de recrutamento. Por outro lado, maiores taxas de recrutamento em relação à mortalidade só têm sido encontradas em florestas com estágios avançados de regeneração após o distúrbio (Oliveira-Filho et al 1997).…”
Section: Discussionunclassified
“…Apesar de termos encontrado mortalidade dependente do tamanho, a estrutura diamétrica da floresta não foi alterada mesmo na área que queimou mais vezes. Resultados similares foram encontrados por Silva et al (2011) que estudaram a dinâmica de fragmentos florestais após enchentes e verificaram a manutenção da estrutura diamétrica da comunidade, uma vez que a frequencia de indivíduos sobreviventes e de mortos nas classes diamé-tricas não diferiu no período monitorado. No PESA, por outro lado, a estrutura vertical foi modificada tanto em Q1 como Q2.…”
Section: Discussionunclassified
“…Além d isso, devido ao processo de silvigênese (MACHADO; OLIVEIRA FILHO, 2010), as taxas de dinâmica não ocorrem de forma constante ao longo do tempo (HIGUCHI et al, 2008a). Porém, poucos trabalhos na região abordam estudos de dinâmica em amb ientes aluviais (GUILHERM E et al, 2004;APPOLINÁ RIO et al, 2005;GUIMA RÃ ES et al, 2008;SILVA et al, 2011a;SILVA et al, 2011b), o que justifica estudos nesses ambientes, por permitirem gerar conhecimentos que podem subsidiar estratégias de manejo e restauração florestal nesses locais.…”
Section: Introductionunclassified